Preparation of Activated Carbons from Hemicellulose Pre-Extraction Residue of Eucalyptus Heartwood and Sapwood and their Application in Toluene Adsorption - Xixiang Huang; Yuanyuan Zhao; Zhiwei Wang; Yanhong Wang; Yun Zhou; Hao Cheng; Penghui Li; Shubin Wu (BioResources)
Pre-extraction of hemicellulose from eucalyptus heartwood and sapwood was conducted using the method of KOH extraction. Activated carbons (ACs) with high toluene adsorption capacity were prepared by using KOH as activator and hemicellulose-pre-extracted residue (HPR) as AC precursor. The findings indicated that the pore structure of the ACs could be regulated by adjusting the carbonization temperature. Using the HPR of eucalyptus heartwood as raw material, the activated carbon carbonized at 400 °C exhibited the highest BET surface area (3699 m2·g-1) and pore volume (1.90 cm3·g-1). The adsorption capacity of AC for toluene reached 816 mg·g-1. The results showed that the adsorption capacity of toluene was associated with the micropores (< 2 nm) in the AC. Optimizing the carbonization temperature could enhance the proportion of micropores, thereby significantly enhancing the activated carbon’s adsorption capacity for toluene.